The Global Dimension of Economic Evolution Knowledge Variety and Diffusion in Economic Growth and Development - Dopfer, Kurt (Physica-Verlag HD, 1996)
This volume on evolutionary approaches to economic development and growth is a member of a family of special volumes that Springer has published on Evolu tionary Economics recently. The present volume has excellent predecessors. There is a special volume on "Evolution in Markets and Institutions", edited by Ulrich Witt, and another on "Evolutionary and Neoclassical Perspectives on Market Structure and Economic Growth", edited by Yannis Katsoulacos. And there are more in the pipeline. The volumes already published reflect the broad ranging interests of evolu tionary economists, and within the scope delineated they are devoted to major research areas of the discipline. The editorial intention behind the venture of special volumes has been to bundle together some of the research areas in order to sharpen the problem focus and to generate research synergies within major research fields. We may, somewhat obviously, define a research field by its research topics. For the present purpose however, we may wish to conceive the research conducted by evolutionary economists as belonging to either a research area that is inspired in its problem perspective by neoclassical economics or to one that is not. The very success of the critique of the neoclassical paradigm relied on a preoccupation with its research scope and questions. Evolutionary econom ics has scored marvelously in challenging major neoclassical stands, and neoclassical economics may never be quite the same in the future
Keywords: R & D/Technology Policy; Economic policy; Wachstumstheorie; Evolutorische Wirtschaft; Räumliche Disparität; Wirtschaftsentwicklung; Industriestaaten; Entwicklungsländer; Aufsatzsammlung